Piecewise affine approximations of fluxes and enzyme kinetics from in vivo 13C labeling experiments - Abate, Alessandro; Hillen, Robert C.; Wahl, Sebastian Aljoscha (International Journal of Robust and Nonlinear Control, 2012)
Owing to the ever increasing amount of available information on metabolic networks and, in particular, to the increase in information content from in vivo 13C dynamic labeling experiments, this work investigates the problem of reconstructing dynamic fluxes and enzyme kinetics. The model structure is based on the use of piecewise affine approximations. The optimization procedure at the basis of the model identification is improved by separating the parameter estimation procedure into two different phases. As a first step, a dynamic flux profile in time is reconstructed using functions that are piecewise affine (in time). To achieve scalability for this step, several approaches have been developed and compared. Afterwards, the time-dependent profiles are embedded in the concentration space and the enzyme kinetic functions for single reactions are identified independently. This is an advantage compared with standard complete kinetic network approaches, which are typically characterized by hundreds of parameters, because now only a few need to be optimized simultaneously. Additionally, different kinetic formats can be rapidly compared. The overall approach is demonstrated using an informative in silico experiment. Copyright © 2012 John Wiley & Sons, Ltd.
CRIS-Team Scopus Importer:2022-01-11
Keywords: dynamic; enzyme kinetics; flux analysis; metabolic networks; model identification; piecewise affine models; systems biology